2002
DOI: 10.1093/ptj/82.10.984
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Role-Related Variables to Job Satisfaction and Commitment to the Organization in a Restructured Hospital Environment

Abstract: Background and Purpose. Many factors in today's hospitals can influence how physical therapists view their work experience. Changing roles, with the accompanying stress, and professionalism may contribute to a therapist's perception of his or her job and the organization in which he or she works. In this study, the relationship between changes in physical therapist role behaviors following hospital restructuring and 2 work-related outcomes-job satisfaction and commitment to the organization-was studied. The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 28 publications
(87 reference statements)
4
22
0
4
Order By: Relevance
“…The direct relationships found in this study were consistent with previous research showing that negative relationships exist between role stressors and both affective and normative commitment (Agarwal & Ramaswami, 1993;King & Sethi, 1997;Lopopolo, 2002;Malik & Malik, 2010;Yousef, 2002;Zakari, 2011). Role ambiguity's negative effect on both types of commitment was greater than that of role conflict, adding support to the literature that the two stressors should be studied separately.…”
Section: Theoretical Implicationssupporting
confidence: 91%
See 2 more Smart Citations
“…The direct relationships found in this study were consistent with previous research showing that negative relationships exist between role stressors and both affective and normative commitment (Agarwal & Ramaswami, 1993;King & Sethi, 1997;Lopopolo, 2002;Malik & Malik, 2010;Yousef, 2002;Zakari, 2011). Role ambiguity's negative effect on both types of commitment was greater than that of role conflict, adding support to the literature that the two stressors should be studied separately.…”
Section: Theoretical Implicationssupporting
confidence: 91%
“…A study by Zakari (2011) looked at the effect of role stressors on nursing faculty in an academic setting and found that role conflict was negatively correlated with affective commitment. Similarly, Lopopolo (2002) and Malik and Malik (2010) found that role conflict negatively influenced affective commitment among managers. Both of these studies demonstrated that employees who faced role stress in the form of conflicting roles were less likely to have an emotional attachment to their organizations.…”
Section: Direct Relationships Between Role Conflict and Role Ambiguitmentioning
confidence: 90%
See 1 more Smart Citation
“…These eventually culminate into honored psychological contract that solidly determines employees' behaviors [22], improves satisfaction and reduces physical and psychological stress associated with use of technologies. This extrapolation could be consolidated by [23] and [24], in their report that, the higher levels of stress have been associated with lower organizational commitment. Inversely, higher OC could be associated with lower TNS.…”
Section: Organizational Commitments In Innovative Organizationsmentioning
confidence: 93%
“…La autonomía, es también esencial para la vida profesional, ya que los empleados con autonomía están más propensos a estar satisfechos con su profesión, familia y vida en general, no piensan cambiar de empleo y están menos vulnerables al estrés y al conflicto, tanto en el trabajo como en la vida familiar 133 .…”
unclassified